Predictors of ovarian cancer survival: A population-based prospective study in Sweden - Yang, L; Klint, Å; Lambe, M; Bellocco, R; Riman, T; Bergfeldt, K; Persson, I; Weiderpass, E (Wiley, 2016)
Ovarian cancer is the leading cause of death from gynecologic malignancies among women worldwide. Little is known about reproductive factors or lifestyle determinants and ovarian cancer prognosis. The objective of this study was to examine whether ovarian cancer survival is influenced by reproductive history, anthropometric characteristics, prediagnostic life-style factors and family history of breast or ovarian cancer. The study population consisted of 635 epithelial ovarian cancer (EOC) cases derived from a nationwide population-based case-control study conducted in Sweden between 1993 and 1995. Exposure data on prediagnostic factors of interest were collected through questionnaires at the beginning of the parent study. Clinical data were abstracted from medical records. Cases were followed-up by means of record linkage to nationwide registers until December 31, 2002. Cox proportional hazard regression model was used to estimate the prognostic effect of each factor in terms of hazard ratios (HR) and 95% confidence intervals (CI), following adjustment for age at diagnosis, FIGO tumor stage and WHO grade of tumor differentiation. Tumor characteristics significantly influenced the risk of death from EOC. After adjustment for these, no clear associations were detected between reproductive history (parity, age at first or last birth, oral contraceptive use, age at menarche or menopause), anthropometric characteristics (body size and shape in different periods of life), lifestyle factors before diagnosis (alcohol consumption, smoking and physical activity over lifetime), nor family history of breast cancer or ovarian cancer and EOC survival. Our findings indicate that these prediagnostic factors do not influence the EOC survival. Nevertheless, among women with early stage disease (FIGO stage I and II), there was some indication that overweight in young adulthood or recent years increased the risk of death, while physical activity in young adult life appeared to reduce the risk of death due to EOC.